The Immunity Protection of Central Nervous System Induced by Pseudorabies Virus DelgI/gE/TK in Mice - Lei Xu; Jian-feng Wei; Jun Zhao; Si-yao Xu; Feng-qin Lee; Min-cai Nie; Zhi-wen Xu; Yuan-cheng Zhou; Yuan-cheng Zhou; Ling Zhu (Frontiers in Microbiology, 2022)
Based on a variant strain, we constructed a gE/gI/TK-deleted pseudorabies virus (PRV). A total of 18 female mice were randomized to a vaccination group to receive PRV XJ delgE/gI/TK, a vehicle group to receive Dulbecco’s modified Eagle’s medium, and a mock group to confirm the protection of PRV delgE/gI/TK on the central nervous system in mice. Subsequently, the vaccination and vehicle groups were infected with PRV XJ. The mice in the vehicle group showed more severe neurological symptoms and higher viral loads than those in the vaccination group. The exudation of Evans blue and the expression of tight junction protein showed no difference in all groups. HE staining showed vacuolar neuronal degeneration in the vehicle group brain, but no tissue lesions were observed in the vaccination group. TNF-α, IL-6, and synuclein were upregulated in the brain of mice in the vehicle group, while those were inhibited among mice in the vaccination group. IFN-β, IFN-γ, ISG15, Mx1, and OAS1 showed no difference in the brain between the vaccination and vehicle groups. In addition, TNF-α and IL-6 were inhibited, and antiviral factors were increased in the intestine of the mice in the vaccination group compared to those in the vehicle group. Our study showed that PRV XJ delgE/gI/TK inhibited neurological damage and the inflammation of the intestine and brain induced by PRV and activated the innate immunity of the intestine.